2001
DOI: 10.1038/35069029
|View full text |Cite
|
Sign up to set email alerts
|

Vortex dynamics in superconducting MgB2 and prospects for applications

Abstract: The recently discovered superconductor magnesium diboride, MgB2, has a transition temperature, Tc, approaching 40 K, placing it intermediate between the families of low- and high-temperature superconductors. In practical applications, superconductors are permeated by quantized vortices of magnetic flux. When a supercurrent flows, there is dissipation of energy unless these vortices are 'pinned' in some way, and so inhibited from moving under the influence of the Lorentz force. Such vortex motion ultimately det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
155
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(167 citation statements)
references
References 12 publications
11
155
1
Order By: Relevance
“…The temperature dependence of H irr has also been investigated [31][32][33][34]. For example, two reports of the magnetic irreversibility field have found that H irr scales linearly with the temperature deviation from T c [31,32] but the analysis of H irr reported in two other studies gives a scaling of the form…”
Section: Introductionmentioning
confidence: 92%
“…The temperature dependence of H irr has also been investigated [31][32][33][34]. For example, two reports of the magnetic irreversibility field have found that H irr scales linearly with the temperature deviation from T c [31,32] but the analysis of H irr reported in two other studies gives a scaling of the form…”
Section: Introductionmentioning
confidence: 92%
“…Two important ways to increase critical current density are by the enhancement of the pinning force 30,31 and/or by increasing the crosssectional area fraction. 7 First, we consider the area fraction.…”
Section: X-ray Tomogram Analysis On Voidsmentioning
confidence: 99%
“…[2][3][4][5][6] To take advantage of its T c of 39 K, enhancements of both the upper critical field ͑H c2 ͒ and J c are essential. Attempts to accomplish this have invoked the introduction of numerous techniques including chemical doping, [2][3][4][5][6] irradiation, 7 and various thermomechanical processing techniques. 8,9 Chemical doping is a simple and readily scalable technique.…”
mentioning
confidence: 99%